A Participatory Action Research Approach to Culturally Adapted Psychoeducation and Counseling Booths for Improving Mental Health Literacy in Remote Schools - Arifah Hilmi Fidihani; Eko Harianto; Widyaning Hapsari (KONSELOR, 2026)
This study examined the potential of a culturally tailored, school-based programme to promote early mental health literacy among adolescents at a remote Islamic boarding school in Malaysia. The programme incorporated psychoeducational activities, such as Hope Tree and Anxiety Jar, alongside classroom counselling and reflective booths, designed as low-resource, safe spaces grounded in Mental Health Literacy, Safe Space, and Empowerment Theory. Twenty-seven students participated across two cycles of participatory action research, with sessions lasting approximately 90 minutes. Data collection comprised participatory observations, written reflections, and informal interviews, and was analysed thematically. Results showed that students engaged in reflective exercises, identified stressors from school, peers, and family, and used counselling booths for confidential emotional sharing. For instance, one student reported feeling more at ease writing concerns before discussing them verbally with a teacher. Observations indicated early help-seeking behaviours and acceptance of emotional expression, though these behaviours varied among students. These findings underscore that contextually relevant, low-resource interventions can foster emotional engagement and initial mental health understanding in settings with limited professional support. Despite its short duration and small sample size, the study provides valuable insights for creating culturally responsive interventions in remote schools and points to future research on sustained engagement, involving less-vocal students, and adapting approaches to diverse educational environments.